(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Clean Up and Relax is a laundry shop that began in 2019, with the concept of cleaning, washing of clothes, and relaxation. The business offer laundry care, lawn maintenance, and other tasks that they neither have enough time for nor have the experience to do it. The business was chosen by the researchers because people never considered signing up for a laundry service until they try the service and end up loving it. This study aimed to make every laundry experience easier with affordable packages and make customers relax in the massage chair inside the laundry shop. The researchers applied the descriptive method as a research instrument through the use of test questionnaires that were provided to the test samples of the needs of the laundromat and identify its prospective customers. The researcher had 50 respondents to gather the information that will help identify the needs of the customers on the service pricing, accessibility, and business offering. To develop the market penetration of the business, the researchers created different promotional tools to be aware of whether a similar business already exists. According to the results of the survey, the laundry shop in the area is acceptable because it answers the need of the residences living in condominiums and those living within the vicinity of the laundry shop. Other service offerings offered by the business got a high percentage in terms of the level of acceptability and the given price for it. The researchers also obtained an excellent rating in terms of the level of profitability and payback period within 2 years, with the cost of Php 1,668,407.65. All services and business offerings were suitable to potential customers and accessible in Scout Borromeo, Diliman, Quezon City. Establishing Clean Up and Relax Laundry shop is extremely in demand to the people around the business location because of the accessibility of the customers who wish to purchase packages. Continuous innovation is highly recommendable to compete in this industry. All students, professionals, and residences within the vicinity of the laundry shop are potential customers of the business. The researchers believed that developing services offering and promotional tools to be adopted by low-and middle-income customers to have better and wider market penetration for the business to have a competitive advantage in pricing and services offered and achieve double-digit growth for the first three years.